Quality and tyranny: competing discourses around a compulsory rubric. Issue 8 (16th November 2020) - McKnight, Lucinda; Bennett, Sue; Webster, Scott
Abstract: This article takes the introduction of a compulsory rubric for assessment across all units taught in an arts and education faculty as an opportunity for the identification and discussion of competing discourses around this process. We identify five discourses that complicate those of quality and efficiency in relation to rubrics: imperatives for twenty-first century learning; authentic assessment; Indigenous perspectives; creative praxis and academic freedom. Through describing the resulting discursive conflict we demonstrate what needs to be negotiated in this particular context, for all staff, with implications for those experiencing similar tensions in their own contexts. We also consider what these tensions both enable and constrain for future assessment policy and practice.